BIOCHEMICAL BIOMASS CONTEST OF THE STRAIN OF ARTHROSPIRA (SPIRULINA) PLATENSIS - С. Г. Каракіс; Л. М. Карпов; О. Г. Драгоева; T. І. Лавренюк; В. А. Сагарiц; В. С. Марченко (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2008)
Comparative analysis of biochemical composition of the wild strain S. platensis (Nordst.) Geitl. and its mutants, selected after chemical mutagenesis, has been carried out. It was found out that mutant strains 198B and 27G contain higher quantities of total protein, essential amino acids, c-phycocyanin, allophycocyanin and chlorophyll a than parental wild strain S. platensis. The strain 198B is also characterized by increased content of carotenoids. The revealed biochemical peculiarities of mutant strains suggest that strains 198B and 27G might serve as an additional source of essential amino acids as well as phycobiliproteins and carotenoids. That is why mutant strains 198B and 27G can be considered as the prominent resources of bioactive substance and recommended for further study of their adaptogenic activity.